Bluetooth light control via mobile phone / Akid Azman and Harris Ikhwan Husman - Azman, Akid; Husman, Harris Ikhwan (2015)
In this project is development of Bluetooth light control via mobile phone. The development of digital information has led the rapid change in human lifestyle. The use of electricity is very important as one of the main source of energy that is vital in today modem life. The objective is to make the light much easier to switch on or off and develop virtual lamp application for mobile phone. So, this project is fine combination of Android mobile technology and Arduino software. User can control lamp using android mobile. An application should be installed on android mobile phone to control lamp. User send command by using application. Wireless controlling technique by using Bluetooth technology. This project consists of a Bluetooth receiver. This Bluetooth device connected to the Arduino software which has a decoder. This decoder sends code for respective command sent by user. Then the lamp connected to the circuit will tum on or off depending on the command given. The project mainly consists of android mobile, Bluetooth receiver unit, and Arduino software as microcontroller. From this project student gain new knowledge of the way to make advance technology. This project focuses more on the light control based on its purpose to help minimize energy of the elderly and handicap. This project using the low cost that provide with application and Bluetooth connection between the home appliances. By using the smartphone it can control from certain distance. Other than that, research has been made already before proceed to make this device. Before the Bluetooth connection were made, there are switching the light by using text message. In era 2015, as can be seen everywhere and everyone use smartphone, everyone having their own smartphone. Why do waste our time moving to a place just to switch on or off the lamp while we can use smartphone as light controller.